Optimization of Heparin Monitoring with Anti-FXa Assays and the Impact of Dextran Sulfate for Measuring All Drug Activity - Jean Amiral; Cédric Amiral; Claire Dunois (Biomedicines, 2021)
Heparins, unfractionated or low molecular weight, are permanently in the spotlight of both clinical indications and laboratory monitoring. An accurate drug dosage is necessary for an efficient and safe therapy. The one-stage kinetic anti-FXa assays are the most widely and universally used with full automation for large series, without needing exogenous antithrombin. The WHO International Standards are available for UFH and LMWH, but external quality assessment surveys still report a high inter-assay variability. This heterogeneity results from the following: assay formulation, designed without or with dextran sulfate to measure all heparin in blood circulation; calibrators for testing UFH or LMWH with the same curve; and automation parameters. In this study, various factors which impact heparin measurements are reviewed, and we share our experience to optimize assays for testing all heparin anticoagulant activities in plasma. Evidence is provided on the usefulness of low molecular weight dextran sulfate to completely mobilize all of the drug present in blood circulation. Other key factors concern the adjustment of assay conditions to obtain fully superimposable calibration curves for UFH and LMWH, calibrators’ formulations, and automation parameters. In this study, we illustrate the performances of different anti-FXa assays used for testing heparin on UFH or LMWH treated patients’ plasmas and obtained using citrate or CTAD anticoagulants. Comparable results are obtained only when the CTAD anticoagulant is used. Using citrate as an anticoagulant, UFH is underestimated in the absence of dextran sulfate. Heparin calibrators, adjustment of automation parameters, and data treatment contribute to other smaller differences.